AIT (allergen immunotherapy): a model for the “precision medicine” - Passalacqua, Giovanni (Clin Mol Allergy, 2015)
The interpretation of medical approaches, especially therapy, evolved rapidly in the last century. Starting from the simple description of symptoms, we moved to the pathophysiological descriptions, to the evidence-based medicine, until the so-called “precision medicine”. This latter can be defined as a structural model aimed at customizing healthcare, with medical decisions/products tailored on an individual patient at a highly detailed level. In this sense, allergen immunotherapy represents an optimal model of “precision medicine”, since we know and describe symptoms, function, aetiological agents at molecular level, and we have the possibility to intervene on the natural history of the disease. If considered under the point of view of pharmaco-economy, that is prescribing the optimal treatment to the right patient, allergen immunotherapy represents an almost-ideal model of precision medicine.